Eficacia comparativa entre Mirabegron vs. Oxibutinina en el tratamiento de Vejiga Hiperactiva - Gutiérrez Flores, José Arturo (2019)
Objective: To determine the comparative efficacy between Oxybutynin and Mirabegron for the treatment of overactive bladder Material and methods: Experimental study, carried out in a group of 30 patients with diagnosis of overactive bladder treated in an outpatient department of the Urology Department of the Víctor Lazarte Echegaray Hospital in the June-December 2018 period. Patients are distributed in two groups randomly, one group will be treated with Mirabegron at a dose of 50 mg daily, and the other group will receive Oxybutynin dose of 5 mg daily, for a period of 2 months, using the Collection Card Data and the Bladder Control Self-Assessment Questionnaire will determine and compare the variation in voiding frequency, and in perception of quality of life, in each patient at the beginning and at the end of the study.